Peningkatkan Hasil Belajar Siswa melalui Penggunaan Media Gambar pada Pembelajaran Perkalian Kelas 2 - Zuliani, Rizki; Lestari, Puji; Safira, Nabila Zahra (Lembaga Yasin AlSys, 2023)
The purpose of this study to address the problem of low student mathematics learning outcomes is to apply a model/strategy that can improve mathematics learning outcomes. So this study aims to examine and find out how the learning process using image media improves learning outcomes in mathematics on multiplication material. The type of research conducted was Classroom Action Research (CAR) with data analysis techniques using a quantitative descriptive approach. The subjects of this study were grade 2 elementary school students at SDN SUDIMARA 2. The results of this study indicated that there was an increase in learning outcomes in teaching effectiveness.